The Implementation of Cooperative Learning with Jigsaw Type to Improve Student Learning Outcomes on Natural Science Subject - Tjandrawati, Tjandrawati (Jurnal Penelitian dan Pembelajaran IPA, 2017)
Abstract The aimed of this research is to know the result of student learning using jigsaw type cooperative learning. The research method used is classroom action research (PTK) with two research cycles. This research was conducted in SMP Negeri 16 Bekasi class VIII.4. The results of the test in the first cycle is still less satisfactory with the number of students who completed 19 people or approximately 41.30% with an average value reached 75, while the minimum Exhaustiveness Criteria (KKM) in the SMP is 78. Improvements made for the implementation of cycle II. The result is obtained as many as 40 students or approximately 78.26% with the average value is 82. The Cooperative learning type jigsaw can improve student learning outcomes in SMP Negeri 16 Bekasi class VIII.4.Keywords: Learning outcomes, Cooperative Learning Type Jigsaw